2022
DOI: 10.36609/bjpa.v30i1.111
|View full text |Cite
|
Sign up to set email alerts
|

Green Human Resource Management Practices and Organizational Citizenship Behaviour towards the Environment in the Banking Sector in Bangladesh

Abstract: The purpose of this study is to investigate the impact of green human resource management practices on organizational citizenship behaviour towards the environment based on the Ability-Motivation-Opportunity (AMO) theory. To support statistical analyses, relevant data were gathered from 132 employees working in the commercial banking sector of Bangladesh. To assess the research model, the PLS-SEM approach was applied using SmartPLS 3.0. The study found a significant positive impact of green training and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The relationships between EXR, EGA, and EGB were investigated using hypotheses H6a and H6b , respectively. The relationships between EXR and EGA were statistically significant, conforming to the study by Sharmin et al [ 31 ] piloted in Bangladesh, which revealed that sustainability-centric employee empowerment, performance appraisal, and training and development significantly improve OCBE. On the other hand, the relationships between EXR and EGB ( H6b ) were found insignificant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The relationships between EXR, EGA, and EGB were investigated using hypotheses H6a and H6b , respectively. The relationships between EXR and EGA were statistically significant, conforming to the study by Sharmin et al [ 31 ] piloted in Bangladesh, which revealed that sustainability-centric employee empowerment, performance appraisal, and training and development significantly improve OCBE. On the other hand, the relationships between EXR and EGB ( H6b ) were found insignificant.…”
Section: Discussionsupporting
confidence: 83%
“…The use of renewable energy technology could provide an alternative method of satisfying Bangladesh's expanding energy needs [ 30 ]. Organizational citizenship behaviour toward the environment (OCBE) was positively benefited by sustainability education and training, sustainability-focused assessment methods, and employee autonomy [ 31 ]. Both cognitive and non-cognitive factors, such as - fostering sustainable workplace guidelines and applications, can improve employees' task-related EGB [ 32 ].…”
Section: Previous Literaturementioning
confidence: 99%